Intensity-dependent relaxation of photoconductivity in nanocrystalline titania thin films - Xie, Z; Burlakov, V; Henry, B; Kirov, K; Smith, H; Grovenor, C; Assender, H; Briggs, G; Kano, M; Tsukahara, Y (2006)
We have discovered that the initial rate of the post-illumination decay of photoconductivity in nanocrystalline Ti O2 depends on the intensity of the illumination. The phenomenon is described by hole detrapping processes affected by electrostatic interactions between the trapped holes, and screening of these interactions by free electrons. The analysis allows determination of both the electron concentration and the electron mobility. In our materials, the value of electron mobility μ ≈ 10-6 cm2 V-1 s-1, in good agreement with results obtained by other methods. © 2006 The American Physical Society.